(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless Sensor networks are an growing areas of research. Wireless Sensor Networks are mostly used to monitor targets in the field of interest. One of the most active areas of research in Wireless Sensor Networks is that of coverage. Coverage and Connectivity are two of the most initial issue in the WSN. Coverage in Wireless Sensor Networks is usually defined as a measure of how well the sensing field is monitored or sensors are able to observe the physical space. Connectivity can be defined as the ability of the sensor to reach the data sink. This paper focuses on the coverage issues in the Wireless Sensor Network. Initially, three coverage issues are discussed